2017
DOI: 10.23978/inf.65188
|View full text |Cite
|
Sign up to set email alerts
|

MaRIS - Migration and Refugee Information Studies Research Project

Abstract: According to the statistics of the United Nations High Commissioner for Refugees (UNHCR 2017) from 2015 there were 65.3 million forcibly displaced people around the world. Global migration can be expected to be a large question in the world also in the future, for example, the recent refugee and asylum seekers crises in Europe brought with it a number of challenges on many levels. One of the major challenges is connected to communication and information. The goal of the MaRIS project is to strengthen the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Notwithstanding these considerations, there is still a long way to go in some areas relevant to the inclusion of forced migrants. These include lifelong learning (literacy courses, Portuguese courses, and multilingual resources) (Alvim, 2015; Crawford and Irving, 2013; Cronnelly, 2021; Eskola et al, 2017; Fejes, 2019; Helsingin Kaupunginkirjasto - Yleisten Kirjastojen Keskuskirjasto [Helsinki City Library - Central Library Of Public Libraries], 2016; IFLA, 2002, 2004, 2015, 2020; IFLA/UNESCO, 2001, 2022; PULMAN, 2003; Togores, 2014; UNESCO, 2016; UNESCO Institute for Lifelong Learning, 2022; U.S. Citizenship and Immigration Services, 2006); interaction with school libraries targeting these specific communities (Bolt and Gerasimidou, 2020; IFLA, 2015; IFLA Library Services to People with Special Needs Section, 2017; Paraschiv, 2017; Thomas, 2016; Vincent, 2018; Vincent and Clark, 2020); assistance in finding housing and employment, and promoting health literacy (Audunson et al, 2011; Caidi and Allard, 2005; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; IFLA, 2020; Khoir et al, 2017; Koontz and Gubbin, 2010; Megersa, 2020; Togores, 2014; Yavuzdemir, 2019; Yeon and Lee, 2021); and the integration of forced migrants into library staff (American Library Association Council, 2019; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; IFLA, 2020; Togores, 2014; Welcome To Your Library, 2007; Yeon and Lee, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding these considerations, there is still a long way to go in some areas relevant to the inclusion of forced migrants. These include lifelong learning (literacy courses, Portuguese courses, and multilingual resources) (Alvim, 2015; Crawford and Irving, 2013; Cronnelly, 2021; Eskola et al, 2017; Fejes, 2019; Helsingin Kaupunginkirjasto - Yleisten Kirjastojen Keskuskirjasto [Helsinki City Library - Central Library Of Public Libraries], 2016; IFLA, 2002, 2004, 2015, 2020; IFLA/UNESCO, 2001, 2022; PULMAN, 2003; Togores, 2014; UNESCO, 2016; UNESCO Institute for Lifelong Learning, 2022; U.S. Citizenship and Immigration Services, 2006); interaction with school libraries targeting these specific communities (Bolt and Gerasimidou, 2020; IFLA, 2015; IFLA Library Services to People with Special Needs Section, 2017; Paraschiv, 2017; Thomas, 2016; Vincent, 2018; Vincent and Clark, 2020); assistance in finding housing and employment, and promoting health literacy (Audunson et al, 2011; Caidi and Allard, 2005; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; IFLA, 2020; Khoir et al, 2017; Koontz and Gubbin, 2010; Megersa, 2020; Togores, 2014; Yavuzdemir, 2019; Yeon and Lee, 2021); and the integration of forced migrants into library staff (American Library Association Council, 2019; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; IFLA, 2020; Togores, 2014; Welcome To Your Library, 2007; Yeon and Lee, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has also argued that institutions should seek to captivate forced migrants, especially those who are unfamiliar with the concept and/or what the public library can offer (City of Sanctuary, 2020; Eskola et al, 2017; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; Helsingin Kaupunginkirjasto - Yleisten Kirjastojen Keskuskirjasto [Helsinki City Library - Central Library Of Public Libraries], 2016; IFLA, 2021; IFLA Library Services to People with Special Needs Section, 2017; Leeper, 2017; Lison, 2016; Shepherd et al, 2018; Wang et al, 2020; Yavuzdemir, 2019). This research revealed gaps in the effective and diversified dissemination of the services and products of the libraries studied, namely because they are limited to the Portuguese language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No âmbito da inclusão social destas comunidades, algumas áreas em que as bibliotecas públicas devem apostar são: a divulgação eficaz dos seus serviços e produtos; a tradução de informação prática sobre a comunidade de acolhimento (Bolt and Gerasimidou, 2020;Eskola et al, 2017; IFLA Library Services to People with Special Needs Section, 2017;Lison, 2016;Shepherd et al, 2018); o fomento da educação, da aprendizagem ao longo da vida (Alvim, Volume 5…”
Section: Missão Social Das Bibliotecas Públicasunclassified
“…Não obstante estas considerações, existe ainda um longo caminho a percorrer em algumas áreas relevantes para a inclusão dos migrantes forçados. Entre estas, destacam-se: a aprendizagem ao longo da vida (cursos de alfabetização e de português, recursos multilingues) (Alvim, 2015;Crawford and Irving, 2013;Cronnelly, 2021;Eskola et al, 2017;Fejes, 2019; Helsingin kaupunginkirjasto -Yleisten kirjastojen keskuskirjasto [Helsinki city library -Central library of public libraries], 2016; IFLA, 2002IFLA, , 2004IFLA, , 2015IFLA, , 2020IFLA/UNESCO, 1994, 2001PULMAN, 2003;Togores, 2014;UNESCO, 2016; UNESCO Institute for Lifelong Learning, 2022; U.S. Citizenship and Immigration Services, 2006); a interação com as bibliotecas escolares direcionadas para estas comunidades (Bolt and Gerasimidou, 2020;IFLA, 2015; IFLA Library Services to People with Special Needs Section, 2017; Paraschiv, 2017;Thomas, 2016;Vincent, 2018;Vincent and Clark, 2020); o auxílio na procura de habitação e de emprego e na promoção da literacia para a saúde (Audunson et al, 2011;Caidi and Allard, 2005; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; IFLA, 2020; Khoir et al, 2017;Koontz and Gubbin, 2010;Megersa, 2020;Togores, 2014;Yavuzdemir, 2019;Yeon and Lee, 2021); e a integração de migrantes forçados nas equipas das bibliotecas (American Library Association Council, 2019; Ethnic and Multicultural Information Exchange Round Table (ALA), 2020; IFLA, 2020; Togores, 2014;Welcome To Your Library, 2007;Yeon and Lee, 2021).…”
Section: Aportaciones Españolas Y Portuguesas a La Iconference 2023unclassified